Defining ScMCA1 Co-regulatory Factors that Control Proteostasis - Rambod, Ramina (Université d'Ottawa / University of Ottawa, 2023)
Proteostasis is a network that insures the proper folding, degradation, and trafficking of proteins. Metacaspases have essential role in programmed cell death and other processes that help cell sustain life. For instance, the Saccharomyces cerevisiae metacaspase 1, ScMCA1, regulates insoluble protein aggregates which promote cellular fitness. Previously, our group reported that different vacuolar catabolism proteins such as Lap4, are altered in the absence of ScMCA1. Lap4 (Vacuolar aminopeptidase 1) plays a major role in yeast's selective autophagy pathway to degrade unwanted materials. Additionally, they reported alternations of heat shock proteins, specially Hsp12 in ΔScMCA1 strain. Therefore, we hypothesised that elevation of Hsp12 and Lap4 expression that leads to vacuolar increase and chaperone activity may serve as compensatory mechanisms to manage the clearance of insoluble protein aggregates when ScMCA1 is lost or impaired. Our results support this theory by showing high expression level of Hsp12 and Lap4 in absence of ScMCA1. We observed high insoluble protein aggregation accumulation in ΔScMcA1 strain lacking Lap4/or Hsp12 compared to wildtype (WT), specially when they are stressed. Those strains also exhibited robust vacuolar response possibly to degrade insoluble protein aggregates through autophagy action. As a result, these alternations in proteostasis may be responsible for decreased cell viability observed in ΔScMCA1+ΔLap4 and ΔScMCA1+Hsp12 under stress conditions.
Keywords: Proteostasis; ScMCA1